EFEKTIVITAS KONSELING KLIEN RAWAT JALAN DI BADAN NARKOTIKA NASIONAL PROVINSI LAMPUNG - Theresia Helen Simarmata; Malik Malik (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
Drug problems are not a common problem but are something urgent, complex and a serious threat. As a form of attention from the Indonesian government, the government formed an institution, namely the National Narcotics Agency which has a legal basis, namely Law No. 39 of 2009 concerning drugs in charge of prevention, eradication of abuse and illicit trafficking of psychotropics, precursors, and other addictive substances except materials for tobacco and alcohol. . Drug users are no longer criminals according to PP 25 of 2011 concerning Self-Reporting at the Recipient Institution for Compulsory Reporting (IPWL). In this case, drug users will carry out rehabilitation both outpatient and inpatient with counseling activities. The study used the outpatient method. The purpose of this study was to determine the effectiveness of outpatient counseling at the National Narcotics Agency of Lampung Province. This study uses a qualitative method with a descriptive approach. The results of the study indicate that outpatient client counseling at the National Narcotics Agency of Lampung Province has been quite effective but facilities and infrastructure need to be improved to support the implementation of counseling. In the implementation of counseling, it is inseparable from the supporting aspects, namely having qualified and professional human resources and the use of advice and infrastructure can be maximized by the counselor for good counseling and the inhibiting aspect is related to commitment or the presence of clients who sometimes like to pass the session. Â Key Words: Effectiveness, Counseling, Clients, Outpatient